2010
DOI: 10.1002/pc.20979
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dielectric properties of CuCl2 and ZnCl2 doped polyaniline

Abstract: This article addresses the synthesis and characterization of polyaniline (PANI) both in pure and doped forms with various levels of CuCl 2 and ZnCl 2 in HCl medium where ammonium persulphate was used as an oxidant. Synthesized polymeric materials were characterized spectroscopically (UV-visible spectroscopy, Fourier transform infrared spectroscopy, and Atomic absorption spectroscopy), thermally (Differential scanning calorimetry), and morphologically (Scanning electron microscopy). Free adsorption energy was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…[2,3,[5][6][7][9][10][11][12][15][16][17][18][19][20][21] Absorption bands at 791, 1236, 1294, and 1558 cm −1 are characteristic peaks of the ES form of PANI. [5,6,9,17] The N-H stretching band observed, for 3443 cm −1 of undoped PANI, gradually decreases with Se doping, which might be due to interaction between metal cations and nitrogen atoms in the polymer chain. The peak observed at around 3100 cm −1 is thought to be due to O-H bands, which may have been the result of variations in the humidity of samples during pellet preparation and measurement.…”
Section: Ft-ir Results For Pani and Pani/se Compositesmentioning
confidence: 98%
See 3 more Smart Citations
“…[2,3,[5][6][7][9][10][11][12][15][16][17][18][19][20][21] Absorption bands at 791, 1236, 1294, and 1558 cm −1 are characteristic peaks of the ES form of PANI. [5,6,9,17] The N-H stretching band observed, for 3443 cm −1 of undoped PANI, gradually decreases with Se doping, which might be due to interaction between metal cations and nitrogen atoms in the polymer chain. The peak observed at around 3100 cm −1 is thought to be due to O-H bands, which may have been the result of variations in the humidity of samples during pellet preparation and measurement.…”
Section: Ft-ir Results For Pani and Pani/se Compositesmentioning
confidence: 98%
“…[3,[5][6][7][9][10][11][12][15][16][17][18][19] The peaks in the spectrum of the undoped PANI were observed at 3443 cm −1 (N-H stretching mode), 1558 cm −1 (C=C stretching of the quinoid ring), 1467 cm −1 (C=C stretching of the benzenoid ring), 1385 cm −1 (C-N stretching mode for quinoid units), 1294 cm −1 (C-N stretching mode), 1236 cm −1 (C-N stretching mode for quinoid units), 1096 cm −1 (C-H bending), and 791 cm −1 (C-H stretching). [2,3,[5][6][7][9][10][11][12][15][16][17][18][19][20][21] Absorption bands at 791, 1236, 1294, and 1558 cm −1 are characteristic peaks of the ES form of PANI. [5,6,9,17] The N-H stretching band observed, for 3443 cm −1 of undoped PANI, gradually decreases with Se doping, which might be due to interaction between metal cations and nitrogen atoms in the polymer chain.…”
Section: Ft-ir Results For Pani and Pani/se Compositesmentioning
confidence: 98%
See 2 more Smart Citations
“…As cathode material, polyaniline was doped with various dopants under certain synthesis conditions and could obtain much high specific capacity [17][18][19]. At present, the study of polyaniline doped with zinc ion was mainly focus on the conductivity, the morphology and its molecular structure characterized by various common analytical techniques [20][21][22]. It was scarcely reported that polyaniline doped with zinc ion as cathode material was applied to the secondary batteries.…”
Section: Introductionmentioning
confidence: 99%